Viable acrosome-intact human spermatozoa in the ejaculate as a marker of semen quality and fertility status. Issue 3 (3rd January 2018) - Egeberg Palme, Dorte Louise; Rehfeld, Anders; Bang, Anne Kirstine; Nikolova, Kristiana Alexandrova; Kjærulff, Søren; Petersen, Morten Rønn; Jeppesen, Janni Vikkelsø; Glensbjerg, Martin; Juul, Anders; Skakkebæk, Niels E; Ziebe, Søren; Jørgensen, Niels; et al.
Abstract: STUDY QUESTION: Is it possible, in an unbiased and clinical relevant way, to determine the number of viable acrosome-intact human spermatozoa in ejaculates and to use this as a measure of fertility chances? SUMMARY ANSWER: Image cytometry enables easy and unbiased quantification of viable acrosome-intact spermatozoa and it correlates with semen quality and fertility status. WHAT IS KNOWN ALREADY: The presence of the acrosome and its ability to respond to physiological inducers (e.g. progesterone) in the female reproductive tract at the appropriate time and place is required for fertilization. However, the available assays are labor intensive and therefore not used clinically. STUDY DESIGN, SIZE, DURATION: Washed semen samples and capacitated swim-up fractions from volunteers were used to develop the assay. Subsequently washed ejaculates from patients in fertility treatment ( n = 156), proven fertile men ( n = 54) and volunteers ( n = 10) were assessed to evaluate the number of acrosome-intact spermatozoa in the ejaculate (acrosomal status) and compared to other semen parameters, fertility status, fertility treatments and pregnancy rates. PARTICIPANTS/MATERIALS, SETTING, METHODS: Image cytometry was used to assess the fluorescence intensity of Pisum sativum agglutinin and Propidium iodide. MAIN RESULTS AND THE ROLE OF CHANCE: The assay was validated by inducing the acrosome reaction in swim-up-purified and capacitated spermatozoa with progesterone and ionomycin, and in repeated acrosomal status measurements of washed ejaculates a small coefficient of variation (3.7%) was observed. Men with poor semen quality had fewer viable acrosome-intact spermatozoa in the ejaculate ( P = 0.0012; median 32.6% vs. 49.3%). A large proportion (44%) of normozoospermic men from infertile couples had less than the observed median fraction (46%) of viable acrosome-intact spermatozoa in the ejaculate. Furthermore, the total number of viable acrosome-intact spermatozoa was significantly lower among men with male factor infertility compared to fertile men (median 35 vs. 97 mill, P = 1 × 10 − 7 ). Men from couples going through one or more ICSI cycles had significant fewer viable acrosome-intact spermatozoa than men from couples who only underwent IUI ( P = 0.002; 44.4% vs. 62.0%) and the fraction of viable acrosome-intact spermatozoa appeared better than classical semen parameters in classifying whether or not couples needed ICSI. A positive, although non-significant, tendency toward ongoing pregnancy with an increasing number of viable acrosome-intact spermatozoa was observed ( P = 0.2). LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Even larger cohorts of infertile couples are needed to substantiate the clinical application of the assay in regard to estimation of fertility potential of an individual. WIDER IMPLICATIONS OF THE FINDINGS: The presented assay makes it possible to measure the number of acrosome competent spermatozoa in an ejaculate in a standardized manner and hence may serve as a new biomarker for male fertility. Few spermatozoa in an ejaculate are acrosome competent and it might be a valuable measure when evaluating male reproductive function. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by grants from the Innovation Fund Denmark. M.G. and S.K. work at ChemoMetec, which produces the image cytometer used in the study, M.G. hold shares in the company. The other authors have no conflict of interest.